2015
DOI: 10.4309/jgi.2015.30.7
|View full text |Cite
|
Sign up to set email alerts
|

Construct Development for the FocaL Adult Gambling Screen (FLAGS): A Risk Measurement for Gambling Harm and Problem Gambling Associated with Electronic Gambling Machines

Abstract: This is the first of two papers describing the development of the FocaL Adult Gambling Screen for Electronic Gambling Machine players (FLAGS-EGM). FLAGS-EGM is a measurement approach for identifying gambling risk, a tool that incorporates separate reflective and formative constructs into a single instrument. A set of statements was developed that captured ten constructs associated with gambling risk or which were considered components of problem gambling. Following completion of focus groups with regular slot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Delfabbro and King [ 32 ] argue that certain items attributed as harms are labelled incorrectly; they suggest that chasing losses, gambling to obtain more excitement, or betting above affordable means, are behaviours that lead to harm and not the harms themselves. Schellinck et al [ 33 ]also argue that borrowing money is not a harm, but is in fact a predictor for the harms, debt and relationship conflict. Critical appraisal of the defined harms used in each study is therefore necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Delfabbro and King [ 32 ] argue that certain items attributed as harms are labelled incorrectly; they suggest that chasing losses, gambling to obtain more excitement, or betting above affordable means, are behaviours that lead to harm and not the harms themselves. Schellinck et al [ 33 ]also argue that borrowing money is not a harm, but is in fact a predictor for the harms, debt and relationship conflict. Critical appraisal of the defined harms used in each study is therefore necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Delfabbro and King 32 argue that certain items attributed as harms are labelled incorrectly; they suggest that chasing losses, gambling to obtain more excitement, or betting above affordable means, are behaviours that lead to harm and not the harms themselves. Schellinck et al 33 also argue that borrowing money is not a harm, but is in fact a predictor for the harms, debt and relationship con ict. Critical appraisal of the de ned harms used in each study is therefore necessary.…”
Section: Data Analysis Planmentioning
confidence: 99%
“…Twenty-two studies include data on age, and several of these found that being younger was associated with a higher risk of experiencing gambling harms [39][40][41][42][43][44] . In particular one study found that younger age groups (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were at risk of dependence and social harms 39 , and Ferrara et al 42 found that as well as higher rates of what they label "problematic gambling", younger age groups showed a higher comorbidity with other addictions. In…”
Section: Agementioning
confidence: 99%